(untitled) (Journal of Economic Research & Business Administration, 2021)
This study examined the influence of technology adoption on tax audit in Osun State. This work used the Survey research design, and the source of data was primary which was generated by the administration of well-structured questionnaire which was ranked with five-point Likert scale, 100 copies of questionnaire were randomly distributed amongst staffer of Federal Inland revenue service, Osun state, Osun State internal revenue service and some business owners out of which 75 were filled and returned. Ordinary least square method of regression analysis was used to analyse the data collected. Findings from this analysis showed that the coefficient of determination indicated that technology explains 50% of the total variation in tax compliance while it explains 69% of the total variation in revenue increase. It was established that there was positive relationship between adoption of technology and tax compliance and revenue increase in Osun state. Pearson Correlation matrix shows the direction, significant and strength of the bivariate associations amongst the variables in the study. The study recommended that the Government should invest heavily on technology for the purpose revenue increase, Government should review tax law to reduce tax evasion to barest minimum, and that the tax authority should endeavor to be completing every tax audit at record time. Key words: technology, tax audit, tax administration, tax evasion, tax avoidance.